2014
DOI: 10.5114/pg.2014.40846
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and liver function in children and adolescents with cirrhosis of the liver

Abstract: IntroductionPeople with cirrhosis of the liver are predisposed to developing oral lesions. The occurrence and type of lesion depend on the degree of liver function impairment and its type, and on the severity and duration of systemic diseases. In children, the age at which the early symptoms of liver disease are experienced is also of great importance.AimTo assess the prevalence of oral pathological lesions in children and adolescents with cirrhosis of the liver, and their correlation with the degree of liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 24 publications
1
16
1
3
Order By: Relevance
“…Multiple symptom candidiasis was twice as frequent as in class B than in class A. Its prevalence decreased as albumin levels dropped, which additionally emphasised the impact of malnutrition on infections, mirroring the results of a previous study (11). No oral infections in children and adolescents with CLD were reported.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Multiple symptom candidiasis was twice as frequent as in class B than in class A. Its prevalence decreased as albumin levels dropped, which additionally emphasised the impact of malnutrition on infections, mirroring the results of a previous study (11). No oral infections in children and adolescents with CLD were reported.…”
Section: Discussionsupporting
confidence: 81%
“…Numerous publications have indicated that chronic liver disease predisposes oral mucosa lesions, which was not unlike the current study (9)(10)(11). We also found that systemic disturbances associated with liver failure may have had a greater impact on oral mucosa and periodontal tissue than the actual causes of liver disease.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Study done by Kowalczyk et al showed oral candidiasis in 28.6% of the cirrhotic patients. 20 Cellulitis was seen in 7% of the patients in our study. In a study done by Rongey et al, cellulitis was seen in 19.3% of the patients.…”
Section: Hepatitis C 7%mentioning
confidence: 46%